Perfectionism and burnout in canoe polo and kayak slalom athletes: The mediating influence of validation and growth-seeking - Hill, A. P.; Hall, H. K.; Appleton, P. R.; Murray, J. J. (The Sport Psychologist, 2010)
Recent research suggests that validation-seeking and dimensions of perfectionism may be antecedents of athlete burnout. The present investigation examined whether validation and growth-seeking mediate the relationship between selforiented and socially prescribed perfectionism and burnout. One-hundred and fifty canoe polo and kayak slalom athletes recruited from the top two divisions in the UK completed measures of validation and growth-seeking (GOI), perfectionism (HMPS), and athlete burnout (ABQ). Analyses supported the mediating role of validation-seeking in the relationship between socially prescribed perfectionism and burnout. However, while bivariate correlations indicated that self-oriented perfectionism was positively related to both validation and growth-seeking, neither mediated the self-oriented perfectionism-burnout relationship. The findings suggest that validation-seeking may be an important psychological factor in the development of burnout for athletes exhibiting high levels of socially prescribed perfectionism. The relationship between self-oriented perfectionism and athlete burnout remains unclear because of its association with multiple motives and with socially prescribed perfectionism.